Algoneurodystrophy following herpes zoster. Issue 765 (July 1989) - Foster, O.; Askaria, A.; Lanham, J.; Perry, D.
Abstract : Algoneurodystrophy frequently follows an identifiable triggering event. It is not widely recognized that herpes zoster can precipitate algoneurodystrophy and three such cases are described here. In one, the affected dermatome did not correspond to the limb involved by the algoneurodystrophy.